Alasan Penghunian Tepian Danau Toba (Pendekatan Kosmologi Batak Atas Makna Religi Tanah, Air, Gunung) - Defri Elias Simatupang (Balai Arkeologi Sumatera Utara, 2008)
AbstractTo use an approach of Batak cosmology according their view about ground, water, and mountain. From those data, it’s hoped this hypothesis shows the factors which is causing Batak people lived in lake side originally